Histories of the present : people and power in Ecuador - Whitten, Norman E., Jr. (Norman Earl), 1937- (University of Illinois Press, 2011)
Drawn from the authors' work over the last twenty years with indigenous populations of Ecuador and catalyzed by the uprising of 1990, this volume takes a multidisciplinary approach to the history of Ecuadorian identity focusing on ethnographic studies, anthropological evaluations of indigenous art and literary analysis to examine the Ecuadorian view of their world. Each essay in the volume includes a prelude discussing its provenance and the intentions of the authors in the development of each piece. The volume includes several figures and maps as well as four full color plates. Norman Whitten is professor emeritus of anthropology and Scott Whitten is a research associate, both at the University of Illinois at Urbana-Champaign. Annotation ©2011 Book News, Inc., Portland, OR (booknews.com).
Keywords: Indians of South America -- Ecuador -- Ethnic identity.; Indians of South America -- Cultural assimilation -- Ecuador.; Indians of South America -- Government relations.; Ethnicity -- Ecuador.; Acculturation -- Ecuador.; Ecuador -- Race relations.; Ecuador -- Social policy.; Peuples autochtones -- Équateur -- Identité ethnique.; Peuples autochtones -- Amérique du Sud -- Relations avec l'État.; Ethnicité -- Équateur.; SOCIAL SCIENCE / General; Acculturation.; Ethnicity.; Indians of South America -- Cultural assimilation.; Indians of South America -- Ethnic identity.; Race relations.; Social policy.; Ecuador.; Indigenes Volk; Soziale Bewegung; Fremdbild; Ethnologie; Schwarze; Ecuador